Students' Stories About Internationalization Efforts in Technical Colleges: Transcending Learning Theories and Institutional Supports - (:unkn) unknown (My University, 2019)
Much of the research regarding internationalization practices pertains directly to four-year institutions, but community colleges are also called to prepare students for participation in an increasing collaborate and interconnected global world (Dellow, 2007; Treat & Hagedorn, 2013). The unique mission of technical colleges, in particular, is positioned to provide opportunities for this type of learning. This global learning curriculum gap at the community college level has also not been widely examined from the student perspective. This research addressed the gaps with regard to two-year technical colleges and student perspective and asks: How do students attending a technical college with an internationalized curriculum connect with the opportunity and assign relevance? Attendant questions included: 1) What aspects of an internationalized curriculum in their course of study draw student interest? 2) What types of learning opportunities in an internationalized curriculum do students suggest help them make connections to their personal lives, workplace or occupational interests? and 3) In what ways, if any, do students assign relevance to the learning experiences in an internationalized curriculum to their personal lives, workplace or occupational interests? Andragogy, transformative learning, and the tenets of global learning were used as a conceptual framework to help understand how these particular students’ lived experiences, roles, and interests extend and enhance the expected outcomes of an internationalized curriculum present in two technical colleges. Each of the 18 students participated in one-one-one interviews. Many also offered an artifact of their learning with a written reflection. These tools granted access to understanding their experiences with internationalized course curriculum. This study yielded three findings. First, students had meaningful connections with internationalized curriculum when they leveraged topics of personal, professional, or academic interest to them. Second, they drew from experiences both inside and outside of the classroom, which reinforced their learning. Third, despite students identifying the application of global learning in their occupations and workplace, they placed a stronger emphasis on working collaboratively with others. Additionally, three master themes of People, Place, and Occupation support the primary findings. Together, these findings and themes have implications for faculty, institutional leadership, and administration while pointing to future research in this area.
Keywords: andragogy; global learning; internationalization; internationalization of curriculum; student experience; technical college